Book Review: Bjarnesen, J. and Turner, S. editors. 2020: Invisibility in African Displacements: From Structural Marginalization to Strategies of Avoidance. (October 2022) - Jordan, Zoë
Bjarnesen, J. and Turner, S. editors. 2020: Invisibility in African Displacements: From Structural Marginalization to Strategies of Avoidance . Africa Now series, The Nordic Africa Institute. London: Zed Books. 312 pp. £24.99. ISBN: 9781786999207 (paperback).